1989
DOI: 10.1002/iroh.19890740507
|View full text |Cite
|
Sign up to set email alerts
|

Field and Laboratory Studies on Nile Phytoplankton in Egypt IV. Phytoplankton of Aswan High Dam Lake (Lake Nasser)

Abstract: Seasonal, local and monthly vertical variations in chlorophyll a concentration and in qualitative and quantitative counts in Aswan High Dam Lake (AHDL) phytoplankton were followed from March 1982 to February 1984. The chlorophyll a values correlated more or less with the total phytoplankton counts. Total algal counts exhibited considerable local variations in the different seasons and tended t o decrease in the most southern part of AHDL, especially during the flood period. The temporal course of algal develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…In this respect, peaks in diatom populations appeared concomitantly with the decrease of water temperature in cooler periods (Mohammed et al . , ; Jasprica & Hafner ). Conversely, diatoms were less abundant in summer, when cyanoprokaryotes were a more important element of the phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, peaks in diatom populations appeared concomitantly with the decrease of water temperature in cooler periods (Mohammed et al . , ; Jasprica & Hafner ). Conversely, diatoms were less abundant in summer, when cyanoprokaryotes were a more important element of the phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
“…The highest population densities of phytoplankton were observed in winter and autumn as a result of the increase of diatoms. In this respect, peaks in diatom populations appeared concomitantly with the decrease of water temperature in cooler periods (Mohammed et al 1986(Mohammed et al , 1989. Conversely, diatoms were less abundant in summer, when cyanoprokaryotes were a more important element of the phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
“…From April to July under stratified conditions the epilimnion usually shows oxygen supersaturation (up to 160 or 200%) in the lacustrine part of the lake (Entz 1997). Mohammed et al (1989) suggested that oxygen concentrations above the saturation level are often resulted by the assimilation activity of the existing phytoplankton. Thermal stratification coincides with the formation of well-oxygenated epilimnion and an oxygen-free hypolimnion layer (Elewa 1980, Latif andElewa 1980).…”
Section: Physico-chemical Analyses and Phytoplankton In Lake Nasser 91mentioning
confidence: 99%
“…Excessive dam and floodgate construction obstruct river flow, resulting in environmental degradation and biodiversity reduction (Berkamp et al 2000). It was revealed that the Aswan Dam has seriously altered the ecological balance of the Nile River Basin and caused a series of environmental disasters such as soil salinity downstream of dam, the shrink of river mouth delta, the schistosomiasis endemic (Mohammed et al 1989;Sadek et al 1997;Selim et al 2002;Stanley and Wingerath 1996). The similar problems also happened in other places such as Kenya (Bartholow et al 2004).…”
Section: Introductionmentioning
confidence: 99%